Recurrent Gastrointestinal Near-Tetraploid Diffuse Large B-Cell Lymphoma Causing Intussusception and Ileal Ulceration. Issue 7 (July 2019) - Mathews, Steven N.; Niec, Rachel; Mathew, Susan; Allan, John N.; Crawford, Carl V.
Abstract : ABSTRACT: Polyploid karyotypes in diffuse large B-cell lymphoma (DLBCL) are rare and carry a poor prognosis. Extranodal polyploid lymphoma is uncommon. A 71-year-old man with back pain was found to have ileal intussusception. He underwent surgical resection and was diagnosed with DLBCL with a near-tetraploid karyotype. Despite rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone therapy, he developed recurrent disease for which he started a clinical trial. He then developed dark stools from an ileal ulcer due to progressive disease and died 2 weeks later. This is the first reported case of gastrointestinal DLBCL with polyploidy. These karyotypes require attention to extranodal disease and prompt initiation of therapy.